The effect of sodium tripolyphosphate (STPP) concentration on the physical and chemical properties of modified yellow pumpkin starch (Modified cucurbita moschata starch) - Faisal, Muhammad; Harianto, Andi; Hutasoit, Jenri Parlinggoman; Amrullah, Shafwan; Ardiansyah, Adi (Jurnal Agrotek Ummat, 2023)
Yellow pumpkin is rich in vitamin A, carotene, and other essential nutrients, and has good durability. Apart from being a food and vegetable, pumpkin can be processed into semi-finished flour which becomes a processed product. This study aims to examine the effect of sodium tripolyphosphate (STPP) concentration on the physical and chemical properties of modified pumpkin starch (Modified cucurbita moschata starch). This study used an experimental method in the laboratory with a completely randomized design (CRD). The concentrations of STPP used in the treatments were 0.1%, 0.3%, 0.5%, 0.7%, and 0.9% of the weight of pumpkin starch. Each treatment was repeated 3 times, totaling 15 experimental units. Parameters observed included solubility, swelling power, moisture content, and starch content. Data were analyzed using analysis of variance (Anova) with a real level of 5% and Least Significance Different (LSD) further test. The results showed that STPP concentration had no significant effect on solubility and swelling power, but had a significant effect on the moisture content and starch content. The higher the STPP concentration, the higher the water content and the lower the starch content. The 0.9% STPP concentration had the highest moisture content (15.54%) and the 0.3% STPP concentration had the highest starch content (92.63%).  In order to be more complex, further research is carried out to test the parameters of phosphate content, ash content, amylose content, amylopectin content, color, PH, viscosity, anthocyanins, crude fiber, gelatinization, syneresis, antioxidants, polyphenols, reducing sugar, water holding capacity and oil holding capacity.